Partial factors for imposed loads in areas for storage and industrial use. Issue 11 (2nd November 2017) - Lenner, Roman; Sykora, Miroslav
Abstract: The procedures for reliability verification of new or existing buildings are calibrated to account for uncertainties and variability of resistance and load parameters. However, present standards often provide a single approach to specification of design values of all imposed loads on buildings without particular distinction between loads associated with considerable uncertainties and well-defined loads. While the former are represented by common loads in office and residential buildings, the latter, including loads due to storage of materials, material handling equipment, machinery or tanks, require different approaches for estimating design values. This contribution identifies the characteristics of well-defined imposed loads and proposes a methodology for calibrating partial factors. Key steps of the methodology consist of assessing static load effect, dynamic amplification if relevant, model uncertainty, sensitivity factors and target reliability. Careful consideration of these influences then yields partial factors that reflect reduced uncertainties in estimating the effects of well-defined imposed loads. It appears that the commonly accepted partial factor of 1.5 in Eurocodes may be reduced. When multiple crossings are considered, the partial factor can be taken independent of the number of crossings while the characteristic value is adjusted. Further studies should be particularly focused on advanced probabilistic modelling of dynamic amplification and of model uncertainties.